The complete mitochondrial genome of marine gastropod Melo melo (neogastropoda: volutoidea). Issue 2 (3rd July 2019) - Zhong, Shengping; Huang, Guoqiang; Liu, Yonghong; Huang, Lianghua
Abstract: Melo melo is an ecologically and economically important species of Neogastropoda, which is an ecologically diverse group of carnivorous marine gastropods. However, the taxonomic classification and phylogenetic studies have so far been limited. In this study, we report the second complete mitochondrial genome of Volutidae from M. melo . The mitogenome has 15, 721 base pairs (68.3% A + T content) and made up of total of 37 genes (13 protein-coding, 22 transfer RNAs and 2 ribosomal RNAs), and a control region. This study was the second available complete mitogenomes of Volutidae and will provide useful genetic information for future phylogenetic and taxonomic classification of Neogastropoda.